What can be expected of the state? Public policy and entrepreneurs during the beginnings of tourist activity in Peru (1930-1950) - Armas Asín, Fernando (2019)
This article analyzes the evolution of public policies for the promotion of tourism in Peru in its early stages, as well as their relationship with local entrepreneurs. It is argued that business people supported such initiatives as long as they did not conflict with their economic interests. When such conflicts occurred, the reaction was predictable. This study contributes to a better understanding of the beginnings of tourism in Peru and the characteristics of its managing agents.